(untitled) (International Journal of Innovative Technologies in Economy, 2022)
The article discusses the problems of food security in the open economy of modern Georgia against the background of the ongoing hostilities between Russia and Ukraine. After the spread of the COVID-19 pandemic, the attention of almost all countries of the world, including Georgia, was focused on self-sufficiency of the demand of their population with local agricultural and food products. In such conditions, Georgia has a chance to expand domestic production of agricultural and food products. In order to increase the competitiveness of the food and nutrition products produced in Georgia, it is necessary to improve the connections between the separate links of their production, to synchronize the production processes. In order to increase the level of food self-sufficiency of Georgia, it is necessary to protect the production of import-substituting, domestic, agrarian products with non-tariff barriers, and to properly manage their production and logistics. Significant and rapid changes in the global supply chain of food and nutrition products provoked by the Covid-19 pandemic have become an opportunity to increase the level of food self-sufficiency of Georgia, which needs to be properly used.